2013
DOI: 10.1007/s00429-013-0531-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of phospholipase C beta isoforms and diaglycerol kinase-beta in rodents cerebella corroborates the division of unipolar brush cells into two major subtypes

Abstract: Sublineage diversification of specific neural cell classes occurs in complex as well as simply organized regions of the central and peripheral nervous systems; the significance of the phenomenon, however, remains insufficiently understood. The unipolar brush cells (UBCs) are glutamatergic cerebellar interneurons that occur at high density in vestibulocerebellum. As they are classified into subsets that differ in chemical phenotypes, intrinsic properties, and lobular distribution, they represent a valuable neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 74 publications
2
37
0
Order By: Relevance
“…To classify ON and OFF UBCs using previous histochemical criteria (Diño et al, 1999; Nunzi et al, 2002; Sekerková et al, 2014), we correlated the ON/OFF subtype with the presence or absence of an mGluR1α - activated current (Schwartz et al, 2012). After identifying the response of each cell by glutamate application, the puff pipette was switched to 200 μM (S)-3,5-DHPG, a selective group I mGluR agonist (Fig 4 A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To classify ON and OFF UBCs using previous histochemical criteria (Diño et al, 1999; Nunzi et al, 2002; Sekerková et al, 2014), we correlated the ON/OFF subtype with the presence or absence of an mGluR1α - activated current (Schwartz et al, 2012). After identifying the response of each cell by glutamate application, the puff pipette was switched to 200 μM (S)-3,5-DHPG, a selective group I mGluR agonist (Fig 4 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, UBCs seemed to amplify and prolong multisensory signals from mossy fibers to their target granule cells. However, later immunohistochemical studies revealed two distinct UBC populations: calretinin + UBCs and mGluR1α + UBCs (Nunzi et al, 2002; Diño and Mugnaini, 2008; Sekerková et al, 2014). A recent study characterized intrinsic (nonsynaptic) electrophysiological properties of these subtypes in cerebellum (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They are most numerous in the nodulus (vermal lobules Xa and Xb), ventral uvula (vermal lobule IXd), flocculus, and ventromedial paraflocculus 29 . Additionally, three molecularly distinct UBC subtypes that express either calretinin, metabotropic glutamate receptor 1 α (mGluR1α) or phospholipase Cβ4 (PLCβ4) have been found, each with their own topographical distribution 2933, see REF 34 for a recent review). As UBCs are located primarily in areas related to vestibular and oculomotor function, this suggests that the operation of the cerebellar cortex is not solely related to regional differences in the pattern of inputs and outputs, and that certain areas may contain distinct cell types to allow different computational processes to aid specific functions.…”
Section: Non-uniform Cerebellar Architecturementioning
confidence: 99%
“…It is expressed predominantly in neurons of the central nervous system and is barely detectable in other tissues or cell types [1417]. The PLCβ1 protein catalyzes the formation of inositol 1,4,5-trisphosphate and diacylglycerol from phosphatidylinositol 4,5-bisphosphate (PIP2), which plays an important role in the intracellular signal transduction of extracellular signals, such as metabotropic glutamate.…”
Section: Introductionmentioning
confidence: 99%